2022
DOI: 10.12688/f1000research.124416.1
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I and discoveries of the HLA-K (pseudogene) related to disease severity and progression in patients with spondyloarthritis in Dr. Soetomo General Hospital, a tertiary health care center in Surabaya, Indonesia

Abstract: Background: Spondyloarthritis (SpA) is a chronic inflammatory disease characterized by enthesitis, sacroiliitis, and axial joint involvement. Although the association of HLA with SpA has been widely reported, there have been no studies of HLA type in the Indonesian population within the last 20 years. This study aims to identify the HLA type in SpA patients at Dr. Soetomo General Hospital, Indonesia. Methods: This study used a cross-sectional analytical design with samples that met the criteria for SpA accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Although studies of the correlation between DKK-1 and BMD in SpA have already been reported, there are scant studies comparing these two factors simultaneously, particularly in SpA patients from Indonesia. The major genetic involvement in autoimmune disease, particularly SpA, enables regional variations in disease appearance and development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of the correlation between DKK-1 and BMD in SpA have already been reported, there are scant studies comparing these two factors simultaneously, particularly in SpA patients from Indonesia. The major genetic involvement in autoimmune disease, particularly SpA, enables regional variations in disease appearance and development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%